How Important Are Rats As Vectors of Leptospirosis in the Mekong Delta of Vietnam? - Loan, Hoang Kim (Vector Borne Zoonotic Dis, 2015)
Leptospirosis is a zoonosis known to be endemic in the Mekong Delta of Vietnam, even though clinical reports are uncommon. We investigated leptospira infection in rats purchased in food markets during the rainy season (October) (n=150), as well as those trapped during the dry season (February–March) (n=125) in the region using RT-PCR for the lipL32 gene, confirmed by 16S rRNA, as well as by the microscopic agglutination test (MAT). Results were compared with the serovar distribution of human cases referred from Ho Chi Minh City hospitals (2004–2012) confirmed by MAT (n=45). The MAT seroprevalence among rats was 18.3%. The highest MAT seroprevalence corresponded, in decreasing order, to: Rattus norvegicus (33.0%), Bandicota indica (26.5%), Rattus tanezumi (24.6%), Rattus exulans (14.3%), and Rattus argentiventer (7.1%). The most prevalent serovars were, in descending order: Javanica (4.6% rats), Lousiana (4.2%), Copenageni (4.2%), Cynopterie (3.7%), Pomona (2.9%), and Icterohaemorrhagiae (2.5%). A total of 16 rats (5.8%) tested positive by RT-PCR. Overall, larger rats tended to have a higher prevalence of detection. There was considerable agreement between MAT and PCR (kappa=0.28 [0.07–0.49]), although significantly more rats were positive by MAT (McNemar 29.9 (p<0.001). MAT prevalence was higher among rats during the rainy season compared with rats in the dry season. There are no current available data on leptospira serovars in humans in the Mekong Delta, although existing studies suggest limited overlapping between human and rat serovars. Further studies should take into account a wider range of potential reservoirs (i.e., dogs, pigs) as well as perform geographically linked co-sampling of humans and animals to establish the main sources of leptospirosis in the region.